Diaspora Poetics and Homing in South Asian Women's Writing : Beyond Trishanku. - Jolly, Gurbir Singh (Lexington Books, 2018)
This book looks at women writers from the South Asian region who negotiate Home from the vantage point of in-between space-defined through the mythical concept of Trishanku and the frameworks of migration, historical consciousness, colonialism, interracial experiences, fragmented memories, nostalgia, and hyphenated identities.